Understanding barriers to breast screening: an online survey of non-attenders as part of a service evaluation in the breast screening programme in England - Gemma Hutton; Shuping J. Li; Samantha L. Quaife; Adam Brentnall; Jacqui Cookson; Jacquie Jenkins; Sue Hudson; Sharon Webb; Emma O’Sullivan; Stephen W. Duffy; Judith Offman; Jo Waller (BMC Public Health)
Abstract Background Early detection of breast cancer through organised mammography screening of asymptomatic individuals reduces breast cancer mortality. Breast screening is offered every three years to women aged 50 to 71 years in England. However, over a third of eligible women did not attend in 2022–2023. Understanding reasons for non-attendance is critical to ensuring the effectiveness of the breast screening programme by highlighting ways to improve access to screening. Methods As part of a service evaluation in the NHS Breast Screening Programme (NHSBSP), we conducted a cross-sectional survey using an online questionnaire in February 2024. Participants were non-attenders from 15 NHSBSP services in England. All women invited to breast screening who subsequently did not attend in October or November 2023 and had a valid mobile number recorded on their records received a single text message containing a link to the survey. The online survey gathered demographic and basic screening history information and assessed endorsement of common barriers to breast screening. Descriptive analysis was used to identify the most commonly endorsed barriers and chi-squared tests were used to explore demographic variation in barrier endorsement. Results Overall, 27,729 women were identified as not attending a screening appointment in October or November 2023. Of these, 17,221 had mobile numbers and were sent a text message inviting them to participate in the survey. In total, 1,074/17,221 (6%) participants completed the survey. The most frequently endorsed barriers to breast screening were: difficulties making a convenient appointment (30%), concern that a man may do the mammogram (28%), worry about the mammogram being painful (27%), previously experiencing pain during a mammogram (26%), having too many other things to worry about (25%) and the appointment being located too far away (23%). Endorsement of the most common barriers varied significantly by age, ethnicity, mental health status and disability but not by educational level. Conclusions These findings identify barriers that could be targeted to increase screening uptake including increasing appointment availability and proximity, reinforcing the message that breast screening is a female-only environment as well as developing interventions to reduce and manage pain during breast screening.